A geometric brownian motion for commodity prices - 492921 Hee, Jie Yuan; Yeak, Su Hoe, 1971-; Fakulti Sains (2009)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2009